2002
DOI: 10.1302/0301-620x.84b8.0841199
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface roughness on stem-cement gaps

Abstract: We have compared the interface morphology at the stem-cement interface of standard Charnley stems with a satin finish (Ra = 0.75 μm) with identical stems which had been grit-blasted over their proximal third (Ra = 5.3 μm) to promote a proximal bond. The stems were cemented into cadaver femora using conventional contemporary cementing techniques. After transverse sectioning, we determined the percentage of the perimeter of the stem which had a gap at the interface. There were substantial gaps (mean 31.4 ± 17.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…These findings are consistent with push-out studies in which rougher stems adhered more strongly to cement (Ahmed et al, 1984;Chen et al, 1999;Crowninshield et al, 1998;Shepard et al, 2000). In contrast, this is inconsistent with Race et al (2002), who have reported that grit-blasted surfaces do not adhere as well to cement.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with push-out studies in which rougher stems adhered more strongly to cement (Ahmed et al, 1984;Chen et al, 1999;Crowninshield et al, 1998;Shepard et al, 2000). In contrast, this is inconsistent with Race et al (2002), who have reported that grit-blasted surfaces do not adhere as well to cement.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, as the temperature decreases, compressive radial stress (residual) increases, indicating that the cement mantle shrinks towards the stem due to the combined effect of thermal and bulk shrinkage (Stage 3). The near-zero tensile residual stress observed for Case 1, with stem pre-heating without temperature gradient between the stem and bone (T ¼ 37 1C), suggests that cement polymerizes away from the stem, which can lead to gap formation at the stem-cement interface (Ahmed et al, 1982b;Mann et al, 2007;Race et al, 2002;Wang et al, 1999).…”
Section: Stages Of Volumetric Changes During Cement Polymerizationmentioning
confidence: 97%
“…Great efforts have been made to optimise cement formulation, [11][12] to improve mixing and/or injection, [13][14][15] and to select the best texture for the surface of the implant. 16,17 Despite these efforts, some degree of porosity can still be observed in bone cement mantles. [18][19][20] It has been suggested that porosity can be reduced by thermally influencing the rate of polymerisation of cement by preheating the stem before its insertion into the medullary canal.…”
mentioning
confidence: 99%